Hypertensive portal cholangiopathy due to portal cavernomatous transformation of non-cirrhotic origin: a case report - Frías Ordoñez, Juan Sebastián (2023)
Portal cholangiopathy refers to cholangiographic abnormalities occurring in patients with portal cavernomatosis, being progressive, presenting with symptomatic biliary disease and severe biliary tract abnormalities. And, it represents an infrequent complication of portal hypertension. We describe the case of a 53-year-old man with a long history of non-cirrhotic portal hypertension and portal cavernomatosis, who presented an episode of symptomatic obstructive biliary disease, and studies documented fibrotic tissue of ascendingperiportal extension with extrinsic compression of the distal common bile duct and dilatation of the extra and intrahepatic biliary tract. Therefore, endoscopic retrograde cholangiopancreatography was performed, and palliative treatment with small papillotomy and placement of a plastic biliary endoprosthesis was successful due to the absence of procedural complications, and clinical improvement and biochemical parameters. Finally, the patient was discharged with indication of priority follow-up for periodic replacement of biliary stents, and evaluation by hepatology. Portal cholangiopathy is a rare entity that should be suspected in subjects with portal hypertension of non-cirrhotic origin, with imaging findings of stenosis, angulations or segmental dilatations, its treatment should be individualized, and endoscopic therapy is of choice in symptomatic biliary disease.